Potensi Ekstrak Etanol Kulit Batang Tumbuhan Mangrove (Avicennia spp.) dalam Menghambat Pertumbuhan Bakteri Aeromonas hydrophyla - Darminto; Alimuddin Ali; Iwan Dini (Bionature, 2009)
The aim of this research is to show the potential of tree bark of mangrove (Avicennia sp.) plant asantibacterial to against Aeromonas hydrophyla. This bacterium causes fishery cultivation disease e.g. theMAS (Motile Aeromonads Septicemia). Antibacterial activity test was done using paper diffusion and dilution methods. The research result showed that extract of tree bark of mangrove (Avicennia sp.) plant having potency as antibacterial particularly to the A. hydrophyla.